Efforts to Improve Hospital Organizational Performance Using the Balanced Scorecard - Soka, Stefanus Dhe; Pandie, David B.W; Roga, Anderias Umbu; Beni, Kornelis Nama (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Hospitals, as part of the public service sector, are expected to implement strategies to improve service quality through the evaluation of Balanced Scorecard implementation. This study aims to identify and analyze the implementation of the Balanced Scorecard in improving organizational performance at Prof. Dr. W. Z. Johannes Regional General Hospital, Kupang. This study employed a qualitative research approach involving 16 participants and was supported by secondary data from the Financial and Development Supervisory Agency audit on hospital performance in 2022. The variables examined included financial perspective, customer perspective, internal business process perspective, and learning and growth perspective. The thematic analysis showed that the financial perspective covered hospital performance measurement, the benefits of performance assessment, constraints in financial performance management, and its impact. The customer perspective included patient satisfaction, complaint handling, and comparison of services received. The internal business process perspective highlighted the achievement of minimum service standards and service quality. The learning and growth perspective addressed human resource management, including medical, nursing, midwifery, and other health personnel, as well as hospital support for capacity building. Based on the Financial and Development Supervisory Agency audit data, the organizational performance of Prof. Dr. W. Z. Johannes Regional General Hospital, Kupang, measured using the Balanced Scorecard, was categorized as very good.Keywords: balanced scorecard; organizational performance; regional public service agency; regional general hospital